2019
DOI: 10.1186/s12889-019-6771-8
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of antibiotics for childhood diarrhea case management — Kenya, 2009–2016

Abstract: Background Antibiotics are essential to treat for many childhood bacterial infections; however inappropriate antibiotic use contributes to antimicrobial resistance. For childhood diarrhea, empiric antibiotic use is recommended for dysentery (bloody diarrhea) for which first-line therapy is ciprofloxacin. We assessed inappropriate antibiotic prescription for childhood diarrhea in two primary healthcare facilities in Kenya. Methods We analyzed data from the Kenya Populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…Dysentery, non-dysentery infections and other clinical complications of infections are serious among Kenyans presenting in health facilities without capacity to diagnose and detect bacterial pathogens, compelling clinicians to consider the provision of empirical antibiotic therapy ( 4 , 7 ). In addition, Kenya has no legislation for controlling antibiotic use in animals; further pressure is applied on antibiotic use as growth promoters and not for the treatment of infections of farm animals ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysentery, non-dysentery infections and other clinical complications of infections are serious among Kenyans presenting in health facilities without capacity to diagnose and detect bacterial pathogens, compelling clinicians to consider the provision of empirical antibiotic therapy ( 4 , 7 ). In addition, Kenya has no legislation for controlling antibiotic use in animals; further pressure is applied on antibiotic use as growth promoters and not for the treatment of infections of farm animals ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhegenic E. coli involved in diarrheal diseases is one of the most important of the various etiological agents of diarrhea ( 3 ). In Kenya, over 15% infectious diarrhea cases present in health facilities ( 4 , 5 ) but only half of health facilities are able to detect and diagnose a pathogen, which may be due to lack of or inadequate diagnostic capacity ( 6 ). Thus, indiscriminate antibiotic treatment is crucial for weak individuals with severe dysentery and nondysentery infection without secondary criteria for bacterial infection ( 4 , 7 ) increasing selection pressure of antibiotic resistant strains and decreasing the effectiveness of antibiotics ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we observed that children who had non-bloody diarrhea without ARIs had a lower prevalence (39%) of antibiotics use compared to those who had non-bloody diarrhea with symptoms of ARIs (54%). Similarily, another study from Kenya, also reported a high prevalence of antibacterial use among children who had diarrhea with ARIs compared to those who only had diarrhea [ 28 ]. In Uganda, antibiotics are prescription only medicines [ 29 ], however, there is inadequate enforcement of regulation of access to antibiotics, making them easily available and possible to self-medicate [ 30 ].…”
Section: Discussionmentioning
confidence: 66%
“…The presence of primary care pediatricians and collaborations with behavioral specialists are important considerations to improve the quality of childcare (Okumura, Knauer, Calvin, & Takayama, ). Chronic comorbidities, such as diarrhea, are factors associated with URIs and increase the utilization of healthcare services among children, particularly among those hospitalized for URIs (Mbonye, ; Rhee et al, ). To prevent the increase in cost and improve the utilization of healthcare services, a strong primary care system is required to improve the coordination of pediatric healthcare services.…”
Section: Introductionmentioning
confidence: 99%